Unresolved Crisis in Medical Education - Gilles R.G. Monif; Matthew J. Severin (Hindawi Limited, 1994)
A crisis exists in medical education. Changes in methodology have diverted attention from synthesis to mass accumulation of factual data. The response to this crisis has been largely focused on a shell game involving new pathways and curriculum changes without addressing the critical issue of what constitutes education. The ultimate problem in medical education is a crisis of leadership. Until education is given a priority status and the obligations to teach on the part of medical educators and to learn on the part of students are translated into a creative policy by those who can lead, the wheels of learning will continue to spin without significant progress.